The Effect of Entrepreneurship Education, Creativity and Entrepreneurial Motivation on Entrepreneurial Interest in the Millennial Generation in Makassar City - Dewi, Dewi; Syam, Agus; Jufri, Muhammad (Journal of Applied Business, Taxation and Economics Research, 2024)
This study aims to determine the effect of entrepreneurship education, creativity and entrepreneurial motivation on interest in entrepreneurship in the millennial generation in Makassar City. This research is a quantitative descriptive study with a sample of 224 respondents and then analyzed based on multiple linear regression analysis. Data obtained through observation, documentation, and questionnaires. Based on the results of the study, the three factors (X) simultaneously have a significant influence on the millennial generation's entrepreneurial interest in Makassar City. However, based on a partially significant test, the entrepreneurship education variable (X1) does not have a significant effect on entrepreneurial interest (Y). While the creativity variable (X2) and the entrepreneurial motivation variable (X3) have a significant influence on the millennial generation's entrepreneurial interest (Y).